The endemic mammals of the Democratic Republic of the Congo - Bonobo, Gorilla and Okapi – in ex situ situation in the Zoos of Europe: Inventory, Access and Benefit Sharing. (Indonesian Journal of Conservation, 2022)
In accordance with the implementation of the shutter Access and Benefit Sharing (ABS) and the program on Bioprospection of Convention on the Biological diversity (CBD) and of sub-program 3 of program 9 of the Biodiversity National Conservation strategy (BNCS) of the Congolese Institute for the Nature Conservation (CINC), an online and documentary search made it possible to as by identifying 9 out of 92 European zoos which shelter 248 specimens of CITES endemic animals of DRC –139 Bonobos (62.6%), 68 Gorillas (30.6%) and 15 Okapis (6.8%) in ex situ situation - set out again in useful order between 4 countries: Belgium, old metropolis of the Democratic Republic of Congo, DRC in initials, (95 specimens including 87 bonobos and 8 Okapis) ; France (59 specimens including 42 gorillas and 17 bonobos), Germany (47 specimens including 23 bonobos, 17 Gorillas and 7 Okapis) and the Netherlands (21 specimens including 12 bonobos and 9 gorillas). From these 3 species, Bonobo proves to be the most coveted (62.6%) by the 9 zoos due   to its great adaptation to the ex situ life, of its genetic inheritance similar to that of the man to 98.7% and its use as experimental biological material for the immunology, vaccines, drugs tests and others. To our knowledge, Apenheul Park (the Netherlands), having 12 bonobos, proved to be the single zoo which paid regularly royalties to CINC in order to support in situ conservation of this species in DRC, which is threatened in situ. As for other countries not in rule, an effort of correction is awaited from their share to support the conservation of the afore in situ species.